Application of BP Neural Network and Fixed Effect in the Relationship between CSR and Female Directors - Wenwen Lyu; Ya Gao; Zarina Abdul Salam (Journal of Mathematics)
This study is to illustrate the two-way influencing mechanism of female directors’ gender and corporate social responsibility (CSR) of China’s listed companies. According to an empirical test of 3723 enterprises from 2013 to 2020, it reveals that the presence of female directors—especially female executive directors—contributes to the improvement of CSR. In the stage of back propagation (BP) neural network, the model included the overalls of CSR and macroscopic strategic, fulfillment content, and disclosed technology three dimensions. It randomly selects 100 samples, and via BP neural network, it predicts that the RKS-CSR rating can effectively show that high-CSR lever enhances the presence of female directors in Chinese listed companies and promotes gender balance in directors’ team, thus achieving gender balance and CSR two-way sustainable development.